A heuristic for the relationship between caring coaching and elite athlete performance - Fisher, L. A.; Larsen, L. K.; Bejar, M. P.; Shigeno, T. C. (International Journal of Sports Science & Coaching, 2019)
While the topic of caring coaching and its relationship to performance has been explored by researchers mainly in the UK, it has been neglected in the US with the exception of three studies by Fisher and colleagues. The core problem is a lack of understanding regarding the construct of care and whether coaches can care about athletes in pressure-filled, high-stakes, win-at-all-cost sport contexts. Thus, in this paper, we draw upon the ethic of care first proposed by Gilligan and later developed by Noddings and on results from the aforementioned studies by Fisher and colleagues as well as insights from scholarship in the UK to propose a heuristic of the potential relationship between caring coaching and elite athlete performance. Such a heuristic could be used in future coach development programs.